Antimicrobial activities of endophytic fungi and bacteria from ipomoea aquatica, manihot esculenta, and coleus aromaticus on extended-spectrum beta-lactamase (esbl)-producing escherichia coli and methicillin resistant staphylococcus aureus (mrsa) - Lim Chee Chee (2023)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, University Malaysia Kelantan, in partial requirement on the course DVT55204 - Research Project. Antimicrobial resistance (AMR) is a public health issue in all regions, threatening both human and animal health. Finding and developing new antimicrobial drugs is critical for saving countless lives. Endophytes, a type of microorganism, act as reservoirs for bioactive metabolites with anticancer, antimicrobial, anti-inflammatory, anti-fungal, anti-viral, and other properties, which has makes it an ideal candidate for natural product production and piqued the interest of many researchers looking for new antimicrobial drugs. Hence, this study was conducted to isolate and identify endophytic fungi and bacteria from Ipomoea aquatica (water spinach), Manihot esculenta (cassava), and Coleus aromaticus (Mexican mint), and determine their antibacterial activities on Extended-Spectrum Beta- Lactamase-producing Escherichia coli (ESBL EC) and Methicillin-Resistant Staphylococcus aureus (MRSA), and compare the antimicrobial activity with selected commercial antibiotics. Antimicrobial activity of endophytic bacteria and fungi were tested by using an agar plug diffusion assay. A total of ten isolates of endophytic bacteria and three isolates of endophytic fungi showed antimicrobial properties against MRSA and ESBL-EC. Among these three plants, water spinach and cassava have the most potential endophytes. Four to five endophytes were able to be isolated from the roots and shoots of both plants. The endophytic bacteria showing antimicrobial activities are Bacillus spp. (B. velezensis, B. clarus, B. wledmannii), Staphylococcus spp. (S. caprae, S. capitis, S. epidermidis), VIII Lysinibaccillus spp. (L. boronitolerans, L. macroides, L. pakistanensis) and Calidifontibacillus erzurumensis while Fungus 0, Fungus 1 and Fungus 2 have shown antimicrobial activities toward ESBL-EC and MRSA. These results indicate that these isolated endophytes could be a source of antimicrobial compounds for further investigation. Keywords: AMR, Endophyte, ESBL-EC, MRSA, Natural products